Hubungan Dukungan Orang Tua Dengan Tingkat Kecemasan Remaja Putri Dalam Menghadapi Menarche Di SDN Lampeuneurut Aceh Besar - Balqis Mauliza Rizky; Fauziah Fauziah; Mansuriza Mansuriza (Lembaga Pengembangan Kinerja Dosen, 2025)
Menarche is the first transitional period marked in women, known as the first menstruation (menarche). During menarche, physical and psychological changes occur, such as anxiety and sadness, due to the physical changes in this period. The changes usually include pubic hair, armpit hair, and breast development. This often happens among elementary school students, including those in SDN Lampeuneurut. This study aims to determine the relationship between parental support and the level of anxiety in girls facing menarche in SDN Lampeuneurut. This research employed a quantitative method with a cross-sectional design. The population consisted of 120 female students in grades 5 and 6 at SDN Lampeueneurut who had not yet experienced menarche. The sample was selected using purposive sampling, resulting in 55 respondents who met the inclusion criteria. This research was conducted from June 18th to 20th, 2025. The instruments used were a parental support questionnaire and the STAI (State Trait Anxiety Inventory) of anxiety questionnaire. The data were analyzed using a bivariate statistical test, the Chi-Square test. The research findings indicated a significant relationship between parental support and the anxiety levels of female students in facing menarche, with a p-value of 0.011 (p-value < 0.05). This study concludes that parental support is related to a decrease in the anxiety levels of girls facing menarche. This study recommends that schools provide basic reproductive health education from an early age, especially regarding menarche, and that parents understand the importance of providing emotional, informational, instrumental, and appreciative support.